Clinical Profile of Cataract Patients with Asteroid Hyalosis in a Tertiary Care Centre: A Retrospective Observational Study - Raveena Jeyabalan; T Sangeetha; T Kavya (Journal of Clinical and Diagnostic Research)
Introduction: Asteroid Hyalosis (AH) is an asymptomatic degenerative ocular condition of the vitreous associated with old age. Since vision is rarely affected, the focus is on clinical challenges in impaired optical biometry from light scatter and obscured fundus reflex caused by dense asteroid bodies during cataract surgery and subsequent visual outcomes. Aim: To study the associated factors, visual outcomes and complications in cataract patients with AH. Materials and Methods: This retrospective observational study included 45 patients with AH who underwent cataract surgery at the Ophthalmology Department of RL Jalappa Hospital and Research Centre in Sri Devaraj Urs Academy of Higher Education and Research, Kolar, Karnataka, India. Medical records from January 2023 to June 2024 were reviewed for demographic details, associated factors, axial length, visual outcomes and postoperative complications. Data analysis was performed using Statistical Package for the Social Sciences (SPSS) version 22.0, with the paired t-test applied to assess mean differences in visual acuity before and after surgery. A p-value of <0.05 was considered statistically significant. Results: The majority of patients were aged between 65 and 74 years (40.0%) and were predominantly normotensive (77.8%), non diabetic (71.1%), non smokers (93.3%), and reported no alcohol use. Visual acuity significantly improved postoperatively from a preoperative mean of 1.15±0.64 to 0.11±0.13 at one month follow-up (p-value<0.001). Common complications observed included striae keratopathy (28.9%) and intraocular lens (IOL) pigment dusting (11.1%). A significant inverse correlation was found between axial length and postoperative refraction (r-value=-0.373, p-value=0.012). Conclusion: In this older cohort, cataract surgery significantly improved visual acuity at one month. Mild complications included striae keratopathy and IOL pigment dusting. An inverse correlation between axial length and postoperative refraction observed which reinforces the importance of accurate biometry and potentially adjusted IOL power selection in these patients.